Arbitration and Alternative Dispute Resolution in Medical Disputes Within Sharia-Compliant Hospitals: The Role of Good Faith in Balancing Patient Justice and Professional Protection - Herliana, Herliana; Nugrahenti, Meydora Cahya (Mazahib, 2025)
The expansion of Sharia-compliant hospitals in Indonesia requires a context-specific mechanism for resolving medical disputes. Law No. 17 of 2023 mandates Alternative Dispute Resolution (ADR), including arbitration, that aligns with Islamic legal principles—particularly good faith. This principle, rooted in sincerity, fairness, and respect, underpins Islamic jurisprudence and ensures ethical dispute resolution. This study proposes an ADR framework, specifically arbitration, for Sharia-compliant hospitals grounded in good-faith principles that safeguard patients’ rights while protecting healthcare professionals from unjust claims. Integrating values such as niyyah (sincere intent), ṣidq (honesty), adl (justice), huqūq (respect for rights), amānah (responsibility), and avoidance of ḍarar (harm) fosters trust, fairness, and accountability, thereby sustaining an ethical healthcare environment responsive to both patient welfare and practitioner integrity.